On the detection of natural frequencies and mode shapes of submerged rotating disk-like structures from the casing. (August 2015) - Presas, Alexandre; Valentin, David; Egusquiza, Eduard; Valero, Carme; Seidel, Ulrich
Abstract: To avoid resonance problems in rotating turbomachinery components such as impellers, it is of paramount importance to determine the natural frequencies of these parts when they are under operation. Nevertheless, most of these rotating structures are inaccessible and in some cases submerged and confined. To measure the natural frequencies of submerged impellers from the rotating frame is complicated, because sensors have to be well fixed, withstand with large pressure and centrifugal forces. Furthermore, the signals have to be transmitted to the stationary frame. For this reason it may be advantageous to measure the natural frequencies with sensors placed on the casing. In this paper, the analysis of rotating disk-like structures submerged and confined has been performed from the stationary frame. Previously, an analytical model to determine the natural frequencies and mode shapes of the disk from the rotating frame is presented. Once natural frequencies and mode shapes are obtained in the rotating frame, the transmission to the stationary frame has been deduced. A rotating disk test rig has been used for the experimental study. It consist of a rotating disk that has been excited from the rotating frame with a piezoelectric patch and it response has been measured from both rotating and stationary frame. Results shows that for rotating submerged structures in heavy fluids such as water, not only the structural modes of the rotating part are different than for rotating structures in air, but also the transmission from the rotating to the stationary frame. Highlights: Natural frequencies of a rotating disk submerged have been analyzed from the rotating and from the stationary frame. Disk is excited from the rotating frame with PZT. Measurement from the rotating and from the stationary frame. Transmission from the rotating to the stationary frame is studied. Detection of the natural frequencies and mode-shapes from the stationary frame.